Diversity of Staphylococcus Species Strains Based on Partial kat (Catalase) Gene Sequences and Design of a PCR-Restriction Fragment Length Polymorphism Assay for Identification and Differentiation of Coagulase-Positive Species (S. aureus, S. delphini, S. hyicus, S. intermedius, S. pseudintermedius, and S. schleiferi subsp. coagulans) - Blaiotta, Giuseppe (American Society for Microbiology (ASM), 2010)
A set of degenerate PCR primers was designed and used to amplify and sequence about 75% of the catalase (kat) gene from each of 49 staphylococcal strains. In some strains of Staphylococcus xylosus, S. saprophyticus, and S. equorum, two catalase genes, katA and katB, were found. A phylogenetic tree was generated and showed diversities among 66 partial (about 900-bp) staphylococcal kat nucleotide sequences (including 17 sequences found in GenBank) representing 26 different species. The topology of this tree showed a distribution of staphylococcal species similar, but not identical, to those reported previously based on 16S rRNA, hsp60, sodA, rpoB, tuf, and gap genes. The kat gene sequences were less conserved than those of 16S rRNA, rpoB, hsp60, and tuf genes and slightly more conserved than those of the gap gene. Therefore, kat gene sequence analysis may provide an additional marker for inferring phylogenetic relationships of staphylococci. Moreover, the discrete nucleotide polymorphism revealed in this gene could be exploited for rapid, low-cost identification of staphylococcal species through PCR-restriction fragment length polymorphism (RFLP) analysis. In this study, a PCR-RFLP assay performed by using only the TaqI restriction enzyme was successfully developed for rapid unequivocal identification/differentiation, at species and subspecies levels, of coagulase-positive staphylococci (CPS). The assay was validated by testing the DNA from 100 staphylococcal strains, including reference and wild CPS strains isolated from different environments. This reliable, rapid, and low-cost approach (requiring about 6 h from DNA isolation to the achievement of results and <5 Euros for each strain tested) allowed unambiguous identification of all the strains assayed, including the newly described S. delphini and S. pseudintermedius CPS species.